UPAYA PELESTARIAN HUTAN MANGROVE KECAMATAN LABUHAN MARINGGAI KABUPATEN LAMPUNG TIMUR UNTUK MENINGKATKAN FUNGSI HUTAN MANGROVE - Rita Sugiarti; Achyani Achyani; Muhfahroyin Muhfahroyin (Universitas Muhammadiyah Metro, 2020)
Abstrak: Conservation efforts undertaken by the Sriminosari community have oncreased in the mangrove forest area from 1995 to the present. The need for sustainable conservation efforts to develop the potential of existing resources in mangrove forest. Human and nature live side by side and can not separated so that humant as creatyres that interact with mangrove forests directly in the effort of utilization should have useful knowledge to improve capabilities. This study will discuss the efforts that can be made by the Sriminosari villagers in the preservation of mangrove forests. An extensice literature review was undertaken to abtain conslusions about efforts that could be made to conserve forests. Implecations that can help further research will be discussed in this journal.